Languages for academic purposes and specialized translation - Pisanski Peterlin, Agnes (Scripta manent (Ljubljana), 2019)
Specialized translation and LSP pedagogy share a common interest in cross-cultural and cross-linguistic contact involving texts for specific purposes. Corpus linguistic studies of different types of multilingual corpora may be of importance to researchers working in both fields. The aim of this paper is to explore the connections between language for academic purposes and specialized translation through a corpus study of academic discourse. A small parallel Slovene-English corpus of geography research papers published in a bilingual journal is analysed to examine the adaptations in the translated texts. The results reveal that revoicing occurs in the texts translated into English, as they contain more explicit references to Slovenia to ensure an unambiguous interpretation. The findings also underline the importance of establishing a stronger connection between LSP pedagogy and specialized translator training.
Keywords: academic discourse; adaptacija; adaptation; akademski diskurz; corpus study; korpusna študija; LSP; prevajanje akademskega diskurza; prevajanje strokovnih besedil; specialized translation; strokovni jeziki; translation of academic discourse